PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV PADA KURIKULUM MERDEKA - Dwi Novri Asmara; Ratnawati; Septia Ika Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on problems in learning, namely students' lack of activity, such as students only listening, taking notes, not asking questions, liking to play, talking when the teacher is explaining learning material, and thinking that learning mathematics is a difficult subject. These problems can indirectly affect learning outcomes. So, efforts are needed to use more innovative and interesting learning models to improve student learning outcomes in mathematics subjects. This research aims to obtain information on whether there is an influence of the application of the project based learning model on the mathematics learning outcomes of class IV students. This research is experimental research using a True-Experimental design, with the form of a Posttest Only Control Design. The research location was carried out at SDN 10 Sitiung and SDN 07 Sitiung, Dharmasraya Regency. The research sample consisted of 31 class IV students. The data collection instruments used were observation, tests and documentation. The test consists of 20 multiple choice questions and 5 filled-in questions which have been tested for validity, reliability, distinguishing power and level of difficulty of the questions. The results showed that the average posttest score for the experimental class was 83.00 and the control class was 65.90. Hypothesis testing using the t-test resulted in sig < (0.000 < 0.05), which means the t-test rejected the existence of H0 and accepted the existence of Ha, which means there was an influence of the project based learning model in class IV elementary school.